Exploring the sociocultural determinants of de novo versus de alio entry in emerging industries - York, Jeffrey G.; Lenox, Michael J. (Strategic Management Journal, 2014)
The influence of institutional factors on firm entry has long interested strategy scholars. However, we have limited understanding of how the sociocultural environment, defined as the unwritten, decentralized “rules of the game,” influences founding rates in emergent industries; we know even less about how these noneconomic factors differentially influence entry by new entrepreneurial ( de novo ) firms versus diversifying incumbent ( de alio ) firms. Utilizing a unique dataset on entry in the green building supply industry, we find that, while economic and policy factors are highly correlated with de alio entry, the sociocultural environment exerts a greater influence on de novo firms. Our findings contribute to the literature on corporate demography, institutions and entrepreneurship, and industry emergence . Copyright © 2013 John Wiley & Sons, Ltd.